BRICS’ impact over Brazilian bilateral commercial relations with China - Torres, Marcus Vinícius De Sá (2014)
Which is BRICS’ impact over bilateral commercial relations? Our hypothesis states that the countries’ group creation in 2006 - formed by Brazil, Russia, India China, and, more recently, South Africa - increased commercials trade among them. The research design combines descriptive statistics, paired sample t test and deep case study comparison (Brazil and China) to estimate production goods variation between 2000 and 2013. All data were collected from two sources: one from the Brazilian Ministry of Development, Industries and Exterior Trade (MDIC in Portuguese) and the other one from Interamerican Development Bank (BID in Portuguese). The preliminary results suggest that the mean difference of allocated resources before and after the BRICS’ institution is statistically significant.